Structural chemistry of oximes - Aakeröy, Christer B.; Sinha, Abhijeet Shekhar; Epa, Kanishka N.; Chopade, Prashant D.; Smith, Michelle M.; Desper, John (My University, 2013)
Oximes (RR'C=N-OH) represent an important class of organic compounds with a wide range of practical applications, but a systematic examination of the structural chemistry of such compounds has so far not been carried out. Herein, we report a systematic analysis of intermolecular homomeric oxime•••oxime interactions, and identify hydrogen-bond patterns for four major categories of oximes (R' = -H, -CH[subscript 3], -NH[subscript 2], -CN), based on all available structural data in the CSD, complemented by six new relevant crystal structures. The structural behavior of oximes examined here, can be divided into four groups depending on which type of predominant oxime•••oxime interactions they present in the solid-state; (i) O-H•••N dimers (R[superscript 2][subscript 2](6)), (ii) O-H•••N catemers (C(3)), (iii) O-H•••O catemers (C(2)), and (iv) oximes in which the R' group accepts a hydrogen bond from the oxime moiety catemers (C(6)). The electronic and structural effects of the substituent (R') on the resulting assembly has been explored in detail in order to rationalize the connection between molecular structure and supramolecular assembly.
Keywords: Oximes; Structural chemistry